Evaluation of Mental Foramen with Cone Beam Computed Tomography: A Systematic Review of Literature - Antoinette Pelé; Pierre-Alexandre Berry; Charles Evanno; Fabienne Jordana (Radiology Research and Practice)
Purpose. The aim of this systematic review is to assess whether the anatomy of mental foramen is precisely evaluable with cone beam computed tomography (CBCT) before implantation in humans. Methods. A systematic review was carried out to evaluate the anatomy of mental foramen (size, position, symmetry, anterior loop, and accessory mental foramen or multiple mental foramina). According to Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines, an electronic search of three databases (Medline, Web of Science, and Cochrane Library) was undertaken until June 2020 and was supplemented by manual searching. Two reviewers will independently perform the processes of study inclusion, data extraction, and quality assessment. Systematic reviews, studies about children, and case reports were excluded. Only studies using CBCT to do preoperative evaluation were selected. Results. From 728 potentially eligible articles, 72 were included in the qualitative analysis and quantitative synthesis. This systematic review provided an assessment of the anatomy of the mental foramen. The mental foramen was located mostly between the two premolars (between 50.4% and 61.95%) or apically to the second premolar (from 50.3% to 57.9%). The mean diameter of the mental foramen was bigger in males than in females; the difference between them could reach 0.62 mm. The anterior loop seemed to be longer in males (between 0.87 ± 1.81 and 7.25 ± 2.02 mm) than in females (between 0.81 ± 1.18 and 6.52 ± 1.63 mm) and with the presence of teeth (from 0.91 ± 1.18 to 2.55 ± 1.28 for dentate people and from 0.25 ± 0.61 to 2.40 ± 0.88 mm for edentate population). The anterior loop and the accessory mental foramina were detected more frequently with CBCT than panoramic X-ray: only between 0.0 and 48.6% AMFs detected with CBCT were also seen with panoramic images. Clinical Significance. The mental foramen (MF) is an important landmark for local anesthesia and surgical and implantology procedures. Its location, morphology, and anatomical variations need to be considered to avoid mental nerve injury. The aim of this review is to evaluate the mental foramen using CBCT through a systematic literature review to improve knowledge of this complex area for the clinician.